The Effect of Applying E-Systems Tax on Taxpayers’ Individual Compliance - Sugianto, Sherly; Arfamaini, Revi (International Journal Labs, 2022)
Background: In order to support the achievement of trust and transparency in increasing tax compliance, one of the efforts made by the Directorate General of Taxes is to change policy, namely if previously tax collection was only carried out by an official assessment system, now a self-assessment system is applied. The implementation of this self-assessment system is also supported by the implementation of the e-Taxation System which consists of e-Registration, e-SPT, e-Filing, and e-Billing. Aim: The purpose of this study was to determine whether there was an effect of the implementation of the taxation e-System consisting of e-Registration, e-SPT, e-Filing, and e-Billing on the compliance of individual taxpayers at KPP Pratama Surabaya Pabean Cantikan. Method: This research uses a quantitative scientific approach by using primary data sources in the form of questionnaires and secondary data in the form of data from KPP Pratama Surabaya Pabean Cantikan. The questionnaires were processed as many as 100 with criteria according to research needs. Findings: The results showed that e-Registration, e-Filing, and e-Billing had a significance value of <0.05 indicating a significant effect on individual taxpayer compliance at KPP Pratama Surabaya Pabean Cantikan. On the other hand, e-SPT has a significance value of > 0.05, indicating that it has no significant effect on individual taxpayer compliance at the KPP Pratama Surabaya Pabean Cantikan. This can be because e-SPT still has shortcomings such as being vulnerable to viruses so it can cause loss of tax data.